Implementation of the Combination of Caesar Cipher, Vigenère Cipher, and Vigenère Autokey in a Diary Web Application to Improve Data Storage Security - Muhammad Arifin Sulistiono; Alfin Khalaj Syahruwardi; Fitra Candra Ramadhani; Jefry Sunupurwa Asri (Jurnal Multidisiplin Sahombu, 2026)
Data storage security is a crucial aspect of information systems, as the value and threats to digital data increase. Classical cryptography, such as the Caesar Cipher and the Vigenère Cipher, individually suffer from cryptanalysis attacks, particularly frequency analysis. Therefore, this study aims to analyze the application of the combined Caesar Cipher and Vigenère Cipher algorithms, specifically the Vigenère Autokey variant, as a form of super-encryption to enhance the security of text data storage. The research method used is a literature review with a descriptive-analytical approach, analyzing several relevant previous studies. The analysis results show that the combination of the Caesar Cipher and Vigenère Autokey algorithms can quantitatively improve security, as indicated by the increase in entropy compared to using a single algorithm. Furthermore, this combination remains computationally efficient and does not increase the size of the encrypted data, thus offering potential for application as a lightweight cryptographic solution for securing text data storage. However, previous research still has limitations, particularly in character set support and symmetric key management, which opens up opportunities for further research.